2022
DOI: 10.1681/asn.2021111515
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Changes Urine Supersaturation by Decreasing pH and Increasing Citrate

Abstract: Clinical Trial registry name and registration number: Empagliflozin and Renal Oxygenation in Healthy Volunteers (EMPA-REIN), NCT03093103

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
15
0
3
Order By: Relevance
“…Second, SGLT2i use can increase urinary bicarbonate excretion and thus raise urine pH, as reported in an animal study . However, a study of healthy volunteers treated with empagliflozin, 10 mg, reported lower urinary pH after 4 weeks of treatment . Third, SGLT2i use could reduce stone formation through its anti-inflammatory effects by suppressing the expression of a stone core matrix protein, osteopontin, and markers of kidney injury, inflammation, and macrophages that promote stone formation .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Second, SGLT2i use can increase urinary bicarbonate excretion and thus raise urine pH, as reported in an animal study . However, a study of healthy volunteers treated with empagliflozin, 10 mg, reported lower urinary pH after 4 weeks of treatment . Third, SGLT2i use could reduce stone formation through its anti-inflammatory effects by suppressing the expression of a stone core matrix protein, osteopontin, and markers of kidney injury, inflammation, and macrophages that promote stone formation .…”
Section: Discussionmentioning
confidence: 94%
“…First, an important mechanism is increased urinary citrate excretion with SGLT2i use. One post hoc study of 40 healthy volunteers (27 who received empagliflozin and 13 who received placebo) reported increased urinary citrate excretion by almost 50% in the group receiving empagliflozin after 4 weeks of treatment . Two studies examining dapagliflozin in patients with T2D (n = 44 and n = 50) also reported increased urinary citrate excretion .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the pH-regulating genes of α-intercalated cells (V-ATPases, H + /K + -ATPases, carbonic anhydrases, chloride-bicarbonate exchanger; Supplementary Table S4 ) only carbonic anhydrases 2 and 15 were transcriptionally upregulated in EMPA-treated kidneys ( Figure 6B ) which possibly promote urine acidification in EMPA animals by generating protons in intercalated cells. A cidic urinary pH has been described in healthy volunteers after a 4 weeks empagliflozin treatment ( Harmacek et al, 2022 ) and for canagliflozin in patients with type 2 diabetes ( Li et al, 2020 ). The authors suspected an inhibitory effect of canagliflozin on proximal tubule NHE3 activity, for which a possible interaction with SGLT2 inhibitor empagliflozin has been described in NHE3-KO mice ( Onishi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%